2018
DOI: 10.2185/jrm.2962
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic synovectomy for the treatment of stage II to IV trapeziometacarpal joint arthritis

Abstract: Objective: As a minimal invasive surgery for the treatment of thumb carpometacarpal joint (trapeziometacarpal [TMC]) arthritis, we performed an arthroscopic synovectomy for Eaton stage II to IV arthritis.Patients and Methods: We included patients who were effectively treated with a corticosteroid injection, experienced recurrence of TMC pain, and had no major instability of the TMC. Surgery was performed in 17 female patients. Synovectomy was performed, when possible, using radiofrequency and a shaver. The mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(22 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…We suspected that the pain during traction was caused by vascular insufficiency due to the use of the Chinese finger trap. The maximal traction weight in this study (5 kg) is acceptable in a clinical setting because 4.5 kg (10 pounds) of traction is usually applied for fingers when performing wrist or thumb arthroscopy [ 17 , 19 , 25 ]. However, the traction of the thumb in patients with thumb CMC joint arthritis may exacerbate pain and other symptoms, although these symptoms disappear within a short period in healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We suspected that the pain during traction was caused by vascular insufficiency due to the use of the Chinese finger trap. The maximal traction weight in this study (5 kg) is acceptable in a clinical setting because 4.5 kg (10 pounds) of traction is usually applied for fingers when performing wrist or thumb arthroscopy [ 17 , 19 , 25 ]. However, the traction of the thumb in patients with thumb CMC joint arthritis may exacerbate pain and other symptoms, although these symptoms disappear within a short period in healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…For patients with mild osteoarthritic changes (Eaton classification stage 1 or 2), ligamentoplasty, arthroscopic synovectomy, and first metacarpal osteotomy are selected for thumb CMC joint preservation surgery, whereas, for patients with advanced osteoarthritic changes (Eaton classification stage 3 or 4), arthroplasty such as ligament reconstruction and tendon interposition, arthrodesis, and artificial joint replacement is generally selected as the thumb CMC joint non-preservation surgery. Although the clinical outcome is generally good with each type of treatment [ 30 ], Ogawa et al have reported symptomatic improvement with joint preservation surgery even in patients with advanced osteoarthritic changes [ 25 ]. We believe that joint preservation surgery is preferable for younger patients or those who are involved in heavy labor, although a risk of osteoarthritic change progression exists even after a long-term joint preservation surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-two studies (with 23 sets of data) met the inclusion and exclusion criteria and thus were included in the analysis 28,29,32,38,39,[41][42][43][44][45][46][47][48][49][50][51][52][60][61][62][63][64] to compare postoperative outcomes between the different techniques (►Table 1). In the trapeziectomy versus debridement alone subgroup analysis, the trapeziectomy subgroup contained 16 studies, 28,29,38,39,[41][42][43][45][46][47][48][49]51,52,60,62 and the debridement subgroup contained six studies.…”
Section: Search Selectionmentioning
confidence: 99%
“…They potentially overcome some of the aforementioned issues by avoiding a capsulotomy and more extensive soft tissue disruption while instead preserving the native anatomy to provide stability and potentially an expedited recovery. 32,[38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] Arthroscopy of the small joints of the wrist and hand was first described in the late 1970s. 53 However, its popularity started to rise markedly in 1996 after Menon published the first article on the use of arthroscopy for the first CMC joint.…”
mentioning
confidence: 99%
See 1 more Smart Citation